Effect of soil type on wood chemical constituents and calorific values of 33-year-old Corymbia citriodora - De Lima Vieira, Willyam [UNESP]; Amorim, Erick Phelipe; Freitas, Miguel Luiz Menezes; da Silva Júnior, Francides Gomes; Guerrini, Iraê Amaral [UNESP]; Rossi, Márcio; Longui, Eduardo Luiz (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
Red Latosol (LV), Red Nitosol (NV) and Quartzarenic Neosol (RQ) have different physical and chemical characteristics, as well as water holding capacity. This study aimed to determine how such differences cause changes in wood density, extractives, lignin and holocellulose contents, as well as higher heating value (HHV), lower heating value (LHV) and useful heating value (UHV), in C. citriodora wood. Wood density was lower in NV. We observed differences in chemical constituents of C. citriodora wood in all three soil types. Trees in RQ and LV soils have higher HHV, LHV and UHV values than trees in NV soil. We concluded that wood produced from all three soils is suitable for use in the Brazilian bioenergy market based on HHV values between 16500 and 18000 kJ.kg-1. Studies in the literature describe extractives and lignin as positively related, while holocellulose is negatively related to calorific value. In our study, wood density seems to have had a greater influence on calorific results than chemical constituents. It is possible that better water and nutrient availability from NV soil compared to RQ and LV soils may have led to higher tree growth, resulting in lower density and, hence, lower calorific values.
Keywords: Extractives; Higher heating value; Holocellulose; Lignin; Lower heating value; Wood density